A Milestone in Polish CISG Jurisprudence and Its Significance to the World Trade Community - Jurewicz, Aleksandra (Journal of Law and Commerce, 2009)
This comment analyzes a case from the Polish Supreme Court that, because of its rigorous discussion of many fundamental matters and embodiment of the Court’s effort to make its decision within the framework of the Vienna Convention, serves as a great contribution to the global CISG jurisprudence.